Heterogeneous tree recruitment following disturbance in insular tropical forest, Kingdom of Tonga. (9th September 2016) - Franklin, Janet; Rey, Sergio J.
Abstract: What factors are related to establishment dynamics following disturbance in late-successional versus second-growth tropical forests of the Pacific islands? Are those relationships robust to interannual fluctuations in establishment? In three sites juveniles were enumerated in 30 (5 × 5-m) subplots within 45 × 50-m tree plots in 2004 and 2005, 2.5 and 3.5 y following a Category-3 tropical cyclone (hurricane), in the Vava'u Island Group, Kingdom of Tonga. Recruitment was almost three-fold greater in the second sample period. Spatial pattern of focal species density was related to density of other juveniles, proximity of conspecific adults and canopy cover in the two years using Seemingly Unrelated Regression. Shade-tolerant species were the most abundant recruits in late-successional sites, establishing near-conspecific adults and other juveniles, while shade-establishing species were recruiting in gaps in second-growth forest where they also constitute the canopy trees. This pattern, observed in both years, reinforces divergent successional trajectories for second-growth and late-successional forest.